The Genesis of Samuelson and Solow's Price-Inflation Phillips Curve - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Samuelson and Solow in their 1960 paper in the American Economic Review: Papers and Proceedings were among the first economists to engage with Phillips' famous unemployment/wage-inflation analysis, now referred to as the Phillips curve. They addressed the question of the relevance of Phillips's analysis for the United Kingdom to the United States, and in process formulated the firstunemployment/price-inflation version of the Phillips curve and were the first to interpret the Phillips curve as a menu for policy. Their paper was an informal analysis presented at a conference. The current paper offers a careful reconstruction and assessment of their original formulation, documenting the close relationship between the wage-inflation and price-inflation versions of the Phillips curve. A recent paper of Hall and Hart (2012) that suggests, first, that Samuelson and Solow should have reached different conclusions about the price-Phillips curve on the basis of regression estimates of their own data and, second, that had they done so the "inflationist" course of U.S. macroeconomic policy in the 1960s and 1970s would have been different. With the reconstruction as a background, the current paper demonstrates that Hall and Hart have not grasped the key details of Samuelson and Solow's analysis, and that they ignore the actual context of the paper, so that neither of their suggestions is likely: Samuelson and Solow would have no reason to reach any different conclusion based on Hall and Hart's estimates, and the course of macroeconomic policy is unlikely to have been affected in any case.
Keywords: B22; B23; B31; E31; E61; E63; 330; Phillips curve; Paul A. Samuelson; Robert M. Solow; inflation; unemployment; macroeconomic policy